Camera trap and questionnaire dataset on ecosystem services provided by small carnivores in agro-ecosystems in South Africa - Samual T. Williams; Naudene Maree; Peter Taylor; Steven R. Belmain; Mark Keith; Lourens H. Swanepoel (Data in Brief, 2018)
This dataset includes data derived from camera trap surveys and questionnaire surveys relating to small carnivores in agro-ecosystems in the Vhembe Biosphere Reserve, South Africa. The data were collected as part of the study “Predation by small mammalian carnivores in rural agro-ecosystems: An undervalued ecosystem service?” (Williams et al., 2017a) [1]. Camera trap locations were stratified by land use: settlement, crops, and grazing areas. The camera trap data provide an insight into the ecology of the nine species of small carnivores that were recorded: striped polecat (Ictonyx striatus), honey badger (Mellivora capensis), large-spotted genet (Genetta maculata), African civet (Civettictis civetta), slender mongoose (Galerella sanguinea), Meller's mongoose (Rhynchogale melleri), Selous' mongoose (Paracynictis selousi), white tailed mongoose (Ichneumia albicauda), and dwarf mongoose (Helogale parvula). We also recorded domesticated animals such as domestic cats (Felis catus), domestic dogs (Canis lupus familiaris), and cattle (Bos taurus) on the camera traps. The questionnaire data are comprised of responses of stakeholders to questions regarding the impacts of these species on rural farming communities. In the accompanying data repository hosted on Figshare (doi 10.6084/m9.figshare.4750807, (Williams et al., 2017b) [2]) we provide raw data, along with processed data and R code used to analyse these data to determine the impact of land use and domestic animals on the species richness and occupancy of small carnivores in rural agro-ecosystems (Williams et al., 2017a) [1].